Optimization of Pipe Length Parameters, Number of Valves and Compressor Operations to Reduce Electricity Consumption - Nurhadi, Achmad; Indra Chandra Setiawan (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
Compressed air is a frequently used energy supply tool in industrial processes. Energy audits and energy-saving measures focus only on technical issues that affect energy efficiency. Related operating issues of compressed air systems are rarely addressed towards energy efficiency. Only 21% of participants in the Australian energy audit program recommended energy-saving measures for compressed air systems. The largest electricity consumption in an automotive factory is on the compressor engine which is needed for the pneumatic needs of machines, dies, and jigs so optimizing the parameters of pipe length, number of valves and compressor operation to reduce electricity consumption is needed. The research method uses the Taguchi method and is reviewed by monitoring the Cumulative Sum Control Chart (CUSUM) after conducting experiments. The experimental results on the parameters of pipe length 668 m, number of valves 6 pcs and operational compressor 185 kW are the most optimal parameters to reduce electricity consumption 198,000 kWh / year with the resulting pressure of 5.43 bar and a pressure drop of 1.57 bar